Awareness of HIV/AIDS among rural youth in India: A community based cross-sectional study - Yadav, Sudha B; Makwana, Naresh R; Vadera, Bhavin N; Dhaduk, Kishor M; Gandha, Kapil M (The Journal of Infection in Developing Countries, 2011)
Introduction: More than one third of reported cases of HIV/AIDS in India are among youth and 60 percent of these reside in rural areas. Assessment of the awareness of HIV/AIDS in the youth is important for determining the impact of previous and current awareness programs as well as the need for interventions. This study aimed to assess the knowledge of rural youth regarding HIV/AIDS and to explore the epidemiological determinants of awareness among them. Methodology: A community-based cross-sectional study was conducted among youths aged 15-24 years in rural areas of the Saurashtra region of Gujarat, India. A cluster sampling design was used, surveying 50 subjects from each of 30 clusters. Data was collected through house-to-house visits using a semi-structured questionnaire. Proportions and logistic regression were used for analysis. Results: Out of a total of 1,237 subjects who participated in survey, 60% knew something about HIV. Of those who had heard of HIV, more than 90% subjects knew the modes of transmission and more than 80% were aware of modes of prevention of HIV/AIDS. One fifth of the subjects had misconceptions in relation to HIV/AIDS. On applying multiple logistic regression, age, education, occupation, and mass media exposure were found to be the major determinants of their knowledge with regard to HIV/AIDS. Conclusions: Basic knowledge of HIV/AIDS is still lacking in two fifths of the rural youth. Literacy and media exposure are factors that determine awareness of HIV among them and can be helpful to raise their knowledge regarding this scourge.